Rapid Micropropagation of boesenbergia rotunda (L.) Mansf. kulturpfl. (a Valuable Medicinal Plant) from shoot bud explants - Yusuf, Nor Azma; Annuar, Mohamad Suffian Mohamad; Khalid, Norzulaani (Academic Journals, 2011)
A successful protocol was developed for mass propagation of Boesenbergia rotunda (L.) Mansf. Kulturpfl., an important medicinal plant. Numerous shoots were induced from young shoot bud of B. rotunda mature rhizome on Murashige and Skoog (1962) medium supplemented with 30.0 g/l sucrose, 2.0 g/l gelrite, different concentrations of 6-benzylaminopurine (BAP) and Î±-naphtaleneacetic acid (NAA). Plant medium supplemented with different concentrations of BAP alone or with NAA produced varying degree of multiple shoots. A supplementation of 2.0 mg/l BAP and 0.5 mg/l NAA gave the best result. Ninety percent of the explants induced multiple shoots within 10 to 14 days of inoculation with five maximum numbers of shoots per explant. The numbers of multiple shoots was low during initial subculture but increased after third subculture and were slightly decreased after fourth subculture. Rooting was spontaneous in almost all the treatments after 10 to 14 days of culture. Micropropagated plantlets were successfully acclimatized.